Anesthesia Aspects of Multivisceral Transplantation: A Case Series Study - Khosravi, M B; Naderi-Boldaji, V; Khalili, F; Sahmeddini, M A; Eghbal, M H; Vatankhah, P; Nikoupour, H; Shamsaeefar, A; Tehran, S Ghazanfar (International journal of organ transplantation medicine, 2022)
Postoperative complications like acute and chronic rejection rates, their causes, antibodymediated rejection, infection (site/pathogens), CMV infection, and other complications that occurred during a 6-month follow-up were also recorded. [...]survival rates were also considered (Table 3). Patients presenting for multivisceral transplantation are critically ill, and long-term parenteral nutrition increases the risk of prior venous thrombosis. [...]bedside ultrasound is recommended to identify the target central vein [4]. [...]we measured core body temperature through the esophageal probe and considered a forced-air warming blanket and fluid warmer. Intraoperative Concerns Fluid resuscitation is crucial because of the prolonged operation time, significant blood loss, and excessive third-space losses. [...]conservative fluid management and the application of a pulse counter cardiac output (PICCO) system are the recommended fluid management strategies to restore intravascular volume [6].